On integral equations of Fredholm type for a class of bounded functions on the real line - Bayramoğlu, M.; Jabbarov, I.; Ibrahimova, S. (Methods of Functional Analysis and Topology, 2022)
We consider the problem of extending the notion of a Fredholm integral equation and investigate its solvability in the class of bounded functions on the real line. Розглядається задача розширення поняття iнтегрального рiвняння Фредгольма i дослiджено його розв’язнiсть у класi обмежених функцiй на дiйснiй прямiй.